Social Conflict In Contestation Of Indonesia Election - Agus Machfud Fauzi; Moh Mudzakir; Mohamed Omar Abdulrahim (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2019)
The background of this research is the conflict began with an inharmony between political party leaders and legislators, especially those who have become legislative members and intend to advance again as legislative candidates from the same party. It aims to provide solutions for political parties in the election nomination. It reveals conflict in the preparation of candidates in the elections of 2019. Researchers collect data from political party information and media coverage by comparing news. The method is qualitative with analysis using Paul Conn's conflict structure theory to produce alternative solutions. The results is a difference in expectations and designs between political party leaders and incumbent legislators, according to political party leaders that legislative incumbents need to have an evaluation so they are displaced from candidates for those who were not optimally fighting for political parties, different perspectives of incumbent legislators because they feel have struggled be serious and prepare for second (more) contestation. The legislative incumbent who should be eligible to advance back from the same electoral district then tries to find a new path by advancing again as a legislative candidate by using other political parties. The Conclusion is shifting legislative candidates and changes in the acquisition of election results show the dynamics of political party conflict affect the outcome.